A multi-scale finite element contact model using measured surface roughness for a radial lip seal. (May 2016) - Wenk, Jonathan F.; Stephens, L. Scott; Lattime, Scott B.; Weatherly, David
Abstract: Historically, large computational requirements have left contact modeling approaches unable to combine multiple-length scale effects (comprised by the macro-scale geometry of the component and sub-micron geometry of the surface roughness) into a single deterministic analysis. This work presents a three-dimensional, multi-scale, finite element contact and deformation model for a worn-in radial lip seal. The model includes elastomer bulk geometry and apex surface roughness measured from an experimentally tested elastomer seal. The work describes the modeling method used to simulate the compressed state of the seal. A statistical parameter analysis of both the compressed and uncompressed surface roughness was performed. Results are presented and discussed with respect to their potential impact on modeling efforts and the operating conditions of the seal. Highlights: Measured surface roughness incorporated into 3D FE model of bulk elastomer geometry. Contact modeling used to compress surface roughness and compare to uncompressed state. Statistical analysis of both surfaces to evaluate tribological surface parameters. Potentially new sealing mechanism created by striated roughness pattern on elastomer.